Magnetic resonance imaging of salivary gland tumours: Key findings for imaging characterisation. Issue 139 (June 2021) - Maraghelli, Davide; Pietragalla, Michele; Cordopatri, Cesare; Nardi, Cosimo; Peired, Anna Julie; Maggiore, Giandomenico; Colagrande, Stefano
Highlights: Conventional and advanced MRI shows good accuracy in characterising the most frequent salivary gland neoplasms. Pleomorphic adenoma frequently exhibits high SI on T2W, ADC ≥ 1.4 × 10 −3 mm 2 /s and A-type DCE time/intensity curve. High SI foci on T1W, ADC < 0.9 × 10 −3 mm 2 /s, and B-type DCE time/intensity curve are suggestive for Warthin tumour. Epithelial malignancy usually shows low SI on T2W, ADC between 0.9 and 1.4 × 10 −3 mm 2 /s, and C-type DCE time/intensity curve. Salivary gland lymphoma usually shows very low ADC values (< 0.7 × 10 −3 mm 2 /s). Abstract: Salivary gland tumours are rare, representing only 3% of all head and neck neoplasms, with the parotid gland being the most common site (80 %). The risk of malignancy is inversely proportional to the size of the gland: lesions arising in the sublingual or minor salivary glands are more likely to be malignant, whereas parotid gland neoplasms are mostly benign. Fine needle aspiration cytology and core needle biopsy are considered the most accurate modalities for the diagnosis of a salivary gland neoplasm; however, they are not always conclusive due to procedural sampling errors and for the presence of a cytological / histological overlap between benign and malignant tumours. Moreover, they cannot be easily performed for parotid deep portion localisation. The role of magnetic resonance imaging (MRI) is growing and advanced techniques (diffusion-weighted and dynamic contrast-enhanced perfusion-weighted imaging) can provide useful additional information for the assessment of salivary gland neoplasms. The aim of this review is to present the main MRI and clinical features of salivary gland tumours to improve their comprehensive evaluation and characterisation.